The application and standardisation of the general reasoning group test for pupils in Venda - Tshifularo, Johannes Gogome (My University, 1995)
Refer to the document
Thesis (M.A. (Psychology)) -- University of the North, 1995
Keywords: Group test; Standardisation; Aptitude tests; Psychological tests; Educational tests and measurements -- South Africa